Answer:
[tex]f(x)=-2log(3x)+3[/tex]
Step-by-step explanation:
we have
[tex]f(x)=log(3x)[/tex]
step 1
Reflecting the function f(x) over the x-axis
we know that
To reflect a function about the x-axis, multiply the function by -1
f(x) -----> -f(x)
so
[tex]f(x)=-log(3x)[/tex]
step 2
Stretching the function f(x) vertically by a factor of two
To stretch a function vertically, multiply the function by two
f(x) -----> 2f(x)
[tex]f(x)=-2log(3x)[/tex]
step 3
Shifting the function f(x) up three units
To shift the function up, adds three units to the function
f(x) -----> f(x) +3
[tex]f(x)=-2log(3x)+3[/tex]